ANANALYSIS OF BULLYING BEHAVIOR ON STUDENT CHARACTER DEVELOPMENT AT SMPN 5 GARUT (Case Study at SMPN 5 Garut) - Akmal Catur Pamungkas; Hilmy Nurfaizan AM; Odang Hermanto; Ana Maulana (SAHUR Journal, 2025)
The number of bullying cases among students is very disturbing and worrying in the midst of the learning process at school that researchers found at SMPN 5 Garut. The purpose of the research conducted was to determine the forms and types of bullying behavior, to determine the impact of bullying behavior on the development of student character and to determine the role of school teachers and peers in handling bullying behavior and the formation of positive character of students. The method used in this research is a qualitative approach with a case study, by collecting data using in-depth interviews with sources directly related to bullying behavior such as guidance counseling teachers, student affairs, OSIS children and the location of the research was carried out at SMPN 5 Garut. The results of the research conducted showed that the forms of bullying that occurred at SMPN 5 Garut included verbal bullying, physical bullying and cyber bullying. The impacts resulting from bullying include students becoming anxious, depressed, traumatized and shy. Meanwhile, the role of teachers and peers in efforts to handle and prevent bullying is by conducting anti-bullying socialization, creating a harmonious learning environment and collaborating with students to create a conducive learning atmosphere. This is proven by the effectiveness of the handling carried out by the school, both by guidance and counseling teachers, student affairs, and peers.